Diversity of Mycobacterium tuberculosis Complex Lineages Associated with Pulmonary Tuberculosis in Southwestern, Uganda. (28th June 2021) - Micheni, Lisa Nkatha; Kassaza, Kennedy; Kinyi, Hellen; Ntulume, Ibrahim; Bazira, Joel
Abstract : Uganda is among the 22 countries in the world with a high burden of tuberculosis. The southwestern region of the country has consistently registered a high TB/HIV incidence rate. This study is aimed at characterizing the Mycobacterium tuberculosis complex (MTBC) genotypic diversity in southwestern Uganda. A total of 283 sputum samples from patients with pulmonary tuberculosis were genotyped using specific single nucleotide polymorphism markers for lineages 3 and 4. Most of the patients were males with a mean age of 34. The lineage 4 Ugandan family was found to be the most dominant strains accounting for 59.7% of all cases followed by lineage 3 at 15.2%. The lineage 4 non-Ugandan family accounted for 14.5% of all cases while 4.2% showed amplification for both lineage 4 and lineage 3. Eighteen samples (6.4%) of the strains remained unclassified since they could not be matched to any lineage based on the genotyping technique used. This study demonstrates that a wide diversity of strains is causing pulmonary tuberculosis in this region with those belonging to the lineage 4 Ugandan family being more predominant. However, to confirm this, further studies using more discriminative genotyping methods are necessary.